Narrativas sobre a Guinendade/i: identidade nacional e diversidade étnica na Guiné-Bissau - Amona, Dingana Paulo Faia (2020)
The Guineans are, simultaneously, the same and different, because, if they are equal before the law (The Constitution of the Republic of Guinea-Bissau in article 24), they are different in their origins, cultures and symbologies. It is therefore necessary to recognize the ethnic diversity of the Guinean nation and, above all, to defend the principle that there is no dominant ethnic group in the Guinean territory to the point of superimposing its language and customs on other groups. To this end, the main objective of the present study is to understand how narratives about “national identity” is interlaced from the perspective of unity and diversity. Therefore, a discussion through the actions that, in the case of Guinea-Bissau, emerge from the “national identity”, which will be in debate and analysis from what is understood as Guinendade/i, has been considered in this dissertation. It is also important to point out that this research seeks to mirror the present time mainly in the years 2019-2020 in the legislative and presidential elections, as it was a period that marked the tense identity disputes based on ethnic and regional belonging. Thus, it puts in suspension the narratives about "national unity" that has as its main flag the “Armed Struggle”, which consequently conditions the return to the past in the process of building discourses and identity guidelines. Guided by the ethnographic method through the technique of field research, this research is based on dense description. Thus, the entire discussion on “national identity” relied on the contribution of interlocutors, with whom a fruitful and lasting dialogue was established. It is concluded that it is impossible to make an analysis and debate on the concept of national identity without a discussion on the categories Nation, Nationalism, and that, in the case of Guinea-Bissau, it is also necessary to consider other elements such as the narratives of the “national liberation struggle” past and ethnic variables. The “national identity” in a territorial space of much social and cultural diversity can only be understood from an approach to the individuals and groups that build it over time.